Job Satisfaction of People With Intellectual Disabilities in Integrated and Sheltered Employment: An Exploration of the Literature. Issue 3 (September 2016) - Akkerman, Alma; Janssen, Cees G. C.; Kef, Sabina; Meininger, Herman P.
Abstract: Paying attention to job satisfaction of people with intellectual disabilities, in either integrated or sheltered employment, is important, to increase individual as well as organizational functioning and well‐being. Nevertheless, little is known about job satisfaction of employees with intellectual disabilities and the factors increasing or hindering this. The aim of this study was to explore existing research evidence regarding job satisfaction of people with intellectual disabilities in integrated and sheltered employment settings, and its associated factors. A systematic and comprehensive literature search revealed 13 relevant studies that were examined. Results indicated that people with intellectual disabilities in integrated employment and sheltered employment generally report satisfaction with their jobs. Satisfaction levels appear to be higher in integrated employment. Furthermore it was found that characteristics of the employee and of the employment setting were associated with job satisfaction, as well as social relations, support, and the fit between the employees' needs and the work environment. Advancements can be made with respect to policy and practice of employment of people with intellectual disabilities. To improve their job satisfaction we suggest an integrative approach, taking into account that job satisfaction is an interplay between personal, situational, and social‐cognitive characteristics. This is reflected in current theoretical frameworks in general job satisfaction literature. Future research on job satisfaction of people with intellectual disabilities could profit from developments in general job satisfaction literature and in addition take account of factors particularly relevant to people with intellectual disabilities, the possible impact of comparison processes, and the development of sound measurement methods. Finally, we advocate for greater insight and involvement of people with intellectual disabilities in career related matters, to enhance their self‐determination and motivation and increase satisfaction.